Content, cost, and context: A framework for understanding human signaling systems. Issue 2 (14th March 2019) - Barker, Jessica L.; Power, Eleanor A.; Heap, Stephen; Puurtinen, Mikael; Sosis, Richard
Abstract: Humans frequently perform extravagant and seemingly costly behaviors, such as widely sharing hunted resources, erecting conspicuous monumental structures, and performing dramatic acts of religious devotion. Evolutionary anthropologists and archeologists have used signaling theory to explain the function of such displays, drawing inspiration from behavioral ecology, economics, and the social sciences. While signaling theory is broadly aimed at explaining honest communication, it has come to be strongly associated with the handicap principle, which proposes that such costly extravagance is in fact an adaptation for signal reliability. Most empirical studies of signaling theory have focused on obviously costly acts, and consequently anthropologists have likely overlooked a wide range of signals that also promote reliable communication. Here, we build on recent developments in signaling theory and animal communication, developing an updated framework that highlights the diversity of signal contents, costs, contexts, and reliability mechanisms present within human signaling systems. By broadening the perspective of signaling theory in human systems, we strive to identify promising areas for further empirical and theoretical work.